Pulmonary Function Test among Asymptomatic Male's Smokers and Non-smokers: A Community Study in Denpasar City, Bali - I Made Muliarta (Journal of Global Pharma Technology, 2020)
Background: Smoking chronically affects lung function, The effect and severity changes differ between individuals. It is estimated that six million adults and 100,000 adolescents died each year from tobacco-related health issues. Active smoking by healthy adults has been reported to cause declines in lung function. These differences between cigarette smokers and non-smokers are in direct proportion to the quantity of smoking. Study-related factor associated with pulmonary function in Indonesia, especially in Bali still limited. Aim: This study aims to examine the factor that may be associated with pulmonary function among smokers and non-smokers in Denpasar. All participants were males. Method: This is an analytical study using a case-control method conducted in Denpasar City represented by 592 male respondents. Data collection is done through interviews with structured questionnaires. Demographic data, occupation, residence, body mass index, smoking habit, spirometry examination were documented. Data were analyzed using SPSS IBM 25.0 with univariate and bivariate analysis. Results: Spirometry examination showed 0.2% respondent had obstructive lung disease, 8.3% had restrictive lung disease, and 0.3% combines. This study found the association between smoking status and impaired lung with p-value <0.0001 (3.334 (CI95% 1.898-7.204). Association between pack years above 1.9 also significant with p-value <0.05 4.020 (CI95% 2.638-8.558). Conclusion: A significant association was found between the status of smoking and lungfunction parameters. Pack years also affect towards lung function parameter, especially FEV1%. Keywords: Smoking status, Packyears, Spirometry, Pulmonary functions.